Impurity profiling of methamphetamine synthesised from α‐phenylacetoacetonitrile (APAAN). Issue 1 (18th August 2021) - Langone, Deanna; Painter, Ben; Nash, Clark; Johnston, Martin R.; Kirkbride, K. Paul
Abstract: The rise in popularity of 'designer' precursor compounds for the synthesis of amphetamine‐type stimulants poses a significant challenge to law enforcement agencies. One such precursor is α‐phenylacetoacetonitrile (APAAN). APAAN emerged in Europe in 2010 and quickly became one of the most popular precursors for amphetamine synthesis in that region. Previous literature has identified four APAAN‐specific impurities formed in the synthesis of amphetamine; however, there is currently no research on the use of APAAN in the synthesis of methamphetamine, which is more likely to be employed in a non‐European market. In this study methamphetamine was synthesised via three common clandestine methods: the Leuckart method and two reductive amination methods. We report the identification of five new impurities and two previously identified impurities characteristic for the use of APAAN in the synthesis of methamphetamine. The newly identified impurities were characterised by MS and NMR and determined to be ( E )‐3‐(methylamino)‐2‐phenylbut‐2‐enenitrile, 3‐(methylamino)‐2‐phenylbutanenitrile, 3‐methyl‐2, 4‐diphenylpentanedinitrile, 2‐phenylbutyronitrile and 3‐hydroxy‐2‐phenylbutanenitrile. Abstract : Impurity profiling was carried out on methamphetamine synthesised from the pre‐precursor α‐phenylacetoacetonitrile (APAAN). Three methamphetamine synthesis reactions were tested, and seven characteristic impurities were identified and characterised. Two have been previously identified as markers in amphetamine synthesised from APAAN, and five are newly identified characteristic impurities.